2013
DOI: 10.1038/srep01112
|View full text |Cite
|
Sign up to set email alerts
|

2D Graphene Oxide Nanosheets as an Adhesive Over-Coating Layer for Flexible Transparent Conductive Electrodes

Abstract: In recent, highly transparent and flexible, two-dimensional (2D) graphene oxide (GO) nanosheet has been paid attention for various applications. Due to an existence of a large amount of oxygen functional groups, the single 2D GO nanosheet has an insulating, transparent, highly dispersible in the eco-friendly water, and hydrophilic property that has strong adhesion to the hydrophilic surface, which will be the best candidate for the use of an over-coating layer (OCL) and protecting layer for a conductive nanowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(125 citation statements)
references
References 25 publications
2
123
0
Order By: Relevance
“…Pei et al showed that graphene oxide (GO)-soldered Ag NW network exhibited a R sh of 14 V/& with 88% transmittance at 550 nm, and large stretchability up to 130% [40]. The GO/Ag NW network exhibited a decreased R sh (up to 53%) and improved chemical, light, and thermal stabilities [41]. In brief, the composite materials improve the electrical property of the FTEs either by better welding of nanowire junctions, or by offering new paths for carrier transport, and can also decrease the surface roughness.…”
Section: Flexible Transparent and Conducting Composites Based On Somentioning
confidence: 96%
“…Pei et al showed that graphene oxide (GO)-soldered Ag NW network exhibited a R sh of 14 V/& with 88% transmittance at 550 nm, and large stretchability up to 130% [40]. The GO/Ag NW network exhibited a decreased R sh (up to 53%) and improved chemical, light, and thermal stabilities [41]. In brief, the composite materials improve the electrical property of the FTEs either by better welding of nanowire junctions, or by offering new paths for carrier transport, and can also decrease the surface roughness.…”
Section: Flexible Transparent and Conducting Composites Based On Somentioning
confidence: 96%
“…In addition GO-coatings adhere strongly to underlying surfaces thereby forming an over–coating and a protective layer at the same time (50). This study will thus provide a new approach for future standardization, and risk assessment of coatings on metal alloys for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The shifts of the Ag 3d peaks for the Ag NWs were related to a phase change of the Ag atoms, and the peak shifts toward higher binding energies were attributed to the ionization of the Ag atoms in the Ag NWs. The Ag atoms existing at the surfaces of the Ag NWs were altered from the metal phase to a metal oxide phase due to the movement of electrons from the surfaces of the Ag NWs to the sp 2 orbital of the GONPs, resulting in a shift toward a higher binding energy [17,18]. The phase shift of the Ag atoms did not occur over the entire Ag-NW electrode because the functional groups, including oxygen groups, of the GONPs were only in contact with some parts of the Ag-NW electrode.…”
Section: Methodsmentioning
confidence: 99%